PELATIHAN PENERAPAN FUNGSI MANAJEMEN PADA KOPERASI PEMBERDAYAAN UMMAT DAARUT TAUHID TANGERANG SELATAN - Abdul Rahman Safiih; Nariah; Yakup Hermansyah (Abdi Jurnal Publikasi, 2025)
This Community Service (PkM) activity was carried out by lecturers from the Bachelor of Management Program at Universitas Pamulang as a tangible contribution to strengthening cooperative institutional governance. The main objective of the program was to enhance the managerial capacity of the board members of the Koperasi Pemberdayaan Ummat Daarut Tauhiid (KOPMU-DT) through an intensive training focused on the four fundamental management functions: Planning, Organizing, Actuating, and Controlling (POAC). The activity was conducted in person over two days, on April 19–20, 2025, at DT Peduli Banten Branch Office, Tangerang Selatan. Participants included cooperative board members, managers, and staff. The training methods used included interactive lectures, case studies, cooperative work plan simulations, and structured group discussions. These approaches were chosen to provide both theoretical understanding and practical, context-based skills. Based on the results of the pre-test and post-test, participants' understanding of cooperative management functions increased by 40%. Active engagement was observed throughout the sessions. Feedback collected via questionnaires and closing discussions showed that 90% of participants found the training highly beneficial and applicable, and it encouraged them to adopt more professional governance practices. Participants also proposed follow-up actions such as regular technical assistance and the development of digital systems to strengthen internal control functions.